Epigenetic silencing of DLEC1 correlates with tumor immune microenvironment and predicts immunotherapy prognosis in multiple cancers - Ruijie Ming; Qi Xiong; Shuh-Ying Tan; Lili Li; Shujie Bao; Jianhua Wang; Lijuan Zhao; Xiaoqian He; Zeze Zheng; Yan Wang; Xiaoyu Liu; Jun Tang; et al. (Human Genetics, 2026)
Cancer remains a major health issue globally, with increasing incidence and mortality rates. While immunotherapy has revolutionized cancer treatment, not all patients benefit, urging the identification of predictive biomarkers. This study utilized public datasets and tumor samples to examine the expression and promoter hypermethylation of DLEC1 in normal and tumor tissues, to evaluate its potential as prognostic and immunotherapy marker. In vitro and in vivo experiments on breast cancer (BrCa) cell lines were conducted to explore the functions and mechanisms of DLEC1 . The prognostic significance of DLEC1 downregulation and its impact on immune cell infiltration and immunotherapy efficacy were analyzed using the GEO and TCGA databases. DLEC1 was frequently downregulated and methylated across multiple cancers. In BrCa, expression of DLEC1 inhibited tumor cell proliferation, induced apoptosis, and activated the interferon lambda1 signaling pathway, indicating its important role as a bona fide tumor suppressor and immunoregulator. High DLEC1 expression correlated with better prognosis in several cancer types and with increased immune cell infiltration. Cancer patients with high DLEC1 expression showed improved overall and progression-free survival under immune checkpoint inhibitor therapies, such as anti-CTLA4, anti-PD1 and anti-PDL1. DLEC1 promoter hypermethylation is a promising biomarker for cancer prognosis and potential immunotherapy response prediction. Its expression and promoter hypermethylation status could thus help to guide clinical treatment strategies for cancer patients, particularly of breast cancer.